A Case of Axial Spondyloarthritis without Sacroiliitis - Ümit Seçkin; Hatice Bodur; Filiz Eser (Archives of Rheumatology, 2009)
Our case is an HLA B27-positive 60-year-old female patient who had been suffering from inflammatory back and heel pain for 10 years. While sacroiliitis was not observed on either magnetic resonance imaging or pelvic X-ray, all possible radiographic findings of axial spondylitis and enthesopathy were observed on the radiographs, including bamboo spine and trolley track sign. We thus stress the diagnostic difficulties. (Turk J Rheumatol 2009; 24: 166-9)